Variations on the Fantastic in the Modern Oral Tradition.The Ballad of "Conde Niño" - Vázquez Recio, Nieves (Amaltea. Revista de Mitocrítica, 2018)
This paper examines the ballad of Conde Niño in the modern oral tradition. This is presented as a fusion of supernatural elements, which runs between the magical, the marvelous and the miraculous, full, on the other hand, of mythical and ritual reminiscences, with the updating of «mitemas», remnants of ancient myths. The ballad allows us to assess the persistence and changes of the fantastic in the orality of the 20th century, in relation to his past ascendants, and to debate these concepts that are so diffuse in the contemporary world using a historical approach.
Keywords: Ballad; Conde Niño; magic; marvel; miracle; myth.